Sensory Evaluation System Based on KANSEI Self-Tuning Fuzzy Inference on Spline Function : Acquisition of KANSEI for Persimmon - FUKUDA, Toshio; CHIKAZAWA, Tomoya; SHIMOJIMA, Koji; YAMAGUCHI, Yuji (Transactions of the Japan Society of Mechanical Engineers Series C, 2000)
Human brain mainly performs two kinds of information processes, intelligent process and KANSEI process. KANSEI is used for the sensory test or evaluation in various fields to estimate many things. It is however hard to evaluate ovjects using KANSEI, because KANSEI is including individual subjectivity, vagueness and many-sided. Besides KANSEI depends on time and situation. In this paper, we propose an expression method of KANSEI. This proposed method use self-tuning fuzzy inference on spline membership function to express individual KANSEI. To show the effectiveness of the proposed system, we applied this method to evaluation of ripeness of persimmons. This method will be available to various kinds of sensory evaluating systems.